Language and student learning: Evidence from an ethnographic study in Mozambique - Feliciano Chimbutane; Ritva Reinikka (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This ethnographic study explores the implementation of bilingual education in Mozambique: how it is understood, adapted, and resisted by school directors, teachers, and local officials. Bilingual education uses local languages in early grades before a gradual shift into Portuguese, which most Mozambican children do not speak when entering school. Our study confirms that students participate actively and understand content better in bilingual classes. Regardless of education policy, school directors decide whether or not to form bilingual classes. They report pressure from parents for Portuguese-only instruction because of misunderstanding about the nature of bilingual education, poor resourcing, and fears about students failing tests. Some teachers demonstrate an impressive ability to provide bilingual education despite a lack of training and materials. Others resist and do little to hide their negative attitude. District officers are not able to supply schools with basic materials for local-language teaching. We conclude that bilingual education has lost momentum in Mozambique.
Keywords: 330; bilingual education; local-language teaching; education policy; implementation; ethnography; Mozambique